La-on profile and attitudes of UPV-CAS students, faculty and staff as of first semester 1991-1992. - Santuyo, Barbara Grace
The study determined the profile of the la-on on the basis of their manner of clothing, age weight and facial expressions., It also determined the attitude of UPV-CAS students, faculty and staff towards la-on. The pre-test was given to 70 UPV-SDM students, faculty and staff for validation. The final data was from 162 UPV-CAS students, faculty and staff. Students, faculty and staff have ambivalent attitudes towards la-on. The Mann-Whitney U test at 5 level of significance showed that attitude between male and female faculty members and between male and female staff do not differ. However, male and female students' attitude towards la-on differ. The Kruskal-Wallis one way analysis of variance with one degree of freedom showed that there is no difference in the attitude of males and females towards la-on. La-on are women aged forty (40) and above. They are sterotyped as good and old-fashioned in their maner of clothing. They weigh 101 to 120 lbs. They are serious, hesitant to express freely, and worrying in their facial expressions. They abound in the teaching profession. Librarians are also stereotyped as la-on or likely candidates. La-on are likely to join religious and mahjong groups. They are known to be sensitive to issues of bitter past, age, sex and marriage. However, most of the distinguishing traits can be change. But, one factor that will help people determine who are the la-on is age. Single women aged forty or above are definitely la-on.